Pembinaan Kedisiplinan Belajar Santri Di Pondok Pesantren - Bahtiar, Yuyun; Syaifuddin, Maskur; Khasibah, Nur (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2023)
The purpose of this study aims to determine the management strategy, learning discipline, and supporting and inhibiting factors of Islamic boarding schools in encouraging learning discipline. This study uses qualitative research. To obtain the required data, researchers used data collection techniques including observations, interviews, and documentation. The validity of the data is then checked by adding persistence and triangulation. This research examines the management strategy of Islamic boarding schools in encouraging discipline in learning for students, in this case focusing on the first management strategy of Islamic boarding schools. management of strategic boarding schools.